Musical and Theoretical Basis of Training The Leader of An Amateur Orchestra Team in Universities of Uzbekistan - Mamadjanovich, Najmetdinov Gayrat (European Journal of Life Safety and Stability (2660-9630), 2021)
At the turn, musical educational institutions of Uzbekistan achieved significant success in education and science. However, today Uzbekistan is in great need of professional musicians-performers and leading personnel, and musical art, in turn, needs educational and methodological developments, effective authoring systems and teaching methods for professionals of various specializations and music lovers.